Sunflower rust (Puccinia helianthi Schwein) (literature review) - E. S. Lepeshko (Зерновое хозяйство России)
Diseases caused by fungi, bacteria and viruses are a serious obstacle to high yields of sunflower seeds. One of the most harmful fungi is the rust pathogen (Puccinia helianthi Schw.). Based on the analysis of domestic and foreign scientific literature, there has been presented the information on the history of the study of sunflower rust, the biology of the pathogen, the racial composition of its populations, the pathogenesis of the disease and selection for resistance to this disease in the Russian Federation and in other countries of the world. There has been considered the contribution of G.V. Pustovoit and her students in the development of breeding sunflower material with rust resistance based on interspecific hybridization of cultivated sunflower with wild species. There has been shown the contribution of the researchers W.E Sackston, T.J. Gulay, S. Masirevic and others, who proposed methods for assessing breeding material for resistance to a pathogen, methods of artificial infection of plants in a greenhouse and a field, who developed differentiator lines of the rust races. Currently, when calculating the virulence and race code of Puccinia helianthi, there is used a nomenclature adopted by a special international committee. Recently, there have been reports from different countries of the emergence of new, more aggressive races of the causative agent of sunflower rust. In Russia, the work on the study of this pathogen has also expanded. The scientists have monitored the rust races and revealed the racial composition of the fungus populations on sunflower in the regions with a strong manifestation of the disease (Tambov, Saratov and Lipetsk regions, Krasnodar Area). Based on the studied literature data, there has been made a conclusion that it is necessary to expand and accelerate work on monitoring the racial composition of populations of the rust pathogen in agrocenoses and developing breeding material that is resistant to the identified races.